2017
DOI: 10.3892/ol.2017.7618
|View full text |Cite
|
Sign up to set email alerts
|

Carnosic acid, an inducer of NAD(P)H quinone oxidoreductase 1, enhances the cytotoxicity of β‑lapachone in melanoma cell lines

Abstract: Abstract. NAD(P)H quinone oxidoreductase 1 (NQO1)-dependent antitumor drugs such as β-lapachone (β-lap) are attractive candidates for cancer chemotherapy because several tumors exhibit higher expression of NQO1 than adjacent tissues. Although the association between NQO1 and β-lap has been elucidated, the effects of a NQO1-inducer and β-lap used in combination remain to be clarified. It has previously been reported that melanoma cell lines have detectable levels of NQO1 expression and are sensitive to NQO1-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…Lin et al, 2018 [43] demonstrated the antiproliferative effect of CA in combination with carmustine or lomustine in B16F10 melanoma cells and tumors arising from B16F10 cells xenografted to the back of C57BL/6 mice. Since CA induces NQO1 expression in melanoma cells in vitro, it affects the cell proliferation and sensitizes melanoma cells to other antitumor drugs [12]. Furthermore, it has been shown that CA inhibits the adhesion and migration of melanoma cells at least partially due to the inhibition of epithelial-mesenchymal transition (EMT) and AKT inactivation [16,18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lin et al, 2018 [43] demonstrated the antiproliferative effect of CA in combination with carmustine or lomustine in B16F10 melanoma cells and tumors arising from B16F10 cells xenografted to the back of C57BL/6 mice. Since CA induces NQO1 expression in melanoma cells in vitro, it affects the cell proliferation and sensitizes melanoma cells to other antitumor drugs [12]. Furthermore, it has been shown that CA inhibits the adhesion and migration of melanoma cells at least partially due to the inhibition of epithelial-mesenchymal transition (EMT) and AKT inactivation [16,18].…”
Section: Discussionmentioning
confidence: 99%
“…It seems that CA is not distributed evenly in plant tissues but rather is found predominantly in the aerial parts. It has also been shown that the amount of CA in plants varies based on the ontogenetic stage of the plant and the environmental conditions [12,13,14,15]. Several studies have shown that CA exhibits interesting biological effects such as anti-inflammatory and anti-oxidant activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CA may also function by enhancing the antitumor effects of current chemotherapeutic agents [ 19 ]. CA enhances the cellular cytotoxicity induced by β-lapachone in melanoma [ 15 ], by tamoxifen [ 25 ] and doxorubicin [ 26 ] in breast cancer, and by adriamycin [ 27 ] and arsenic trioxide [ 28 ] in leukemia. In this study, though TMZ could inhibit glioma cell growth, TMZ in combination with low-dose CA was more effective than TMZ alone.…”
Section: Discussionmentioning
confidence: 99%
“…The CA and fisetin combination treatment led to enhanced inhibition of cell growth by inducing apoptosis in lung cancer [ 13 ]. CA enhanced carmustine, lomustine, and β-lapachone-induced cell growth inhibition and cell cycle arrest in melanoma [ 14 , 15 ]. However, the combination effects of CA and TMZ on glioma and the underlying molecular mechanism are still ambiguous.…”
Section: Introductionmentioning
confidence: 99%